Indeonsian Government Bond Stochastic Simulation - Deddy P. Koesrindartoto, Fernando Adventur (ITB, 2011)
This paper proposes a govemment bodn portofolio stochatic simulation using a Vasicek Model, a generally used model of term structure of interest rates. The model is used to generate the possible term strcture of interest rates for five years based on the historical term structure. The future govemment debts are forecasted using ARIMA model, and the efficient frontier of costs resulting from portfolios of bond with different maturity structures are determined from the Cost-at-Risk framwork. An optimization process will be conducted on the govemment bond portfolio efficient frontier based on the govermment risk proference.